Green intellectual capital and green supply chain performance: do external pressures matter? - Mohammed Ibrahim Buhaya; Abdelmoneim Bahyeldin Mohamed Metwally (Cogent Business & Management, 2024)
This paper examines the impact of Green Intellectual Capital (GIC) on Green Supply Chain Performance (GSCP). Further, the study examines the moderating role of external pressures (EP) on the relationship between GIC and GSCP. Data were collected from employees working in Egyptian hotels and tourism companies (N = 366). The collected data were analyzed using smart partial least squares (Smart-PLS) software. The current research indicated that there is a positive and significant impact of all GIC components on GSCP. The results also revealed that EP were found to moderate the relationship between GIC and GSCP. The study model was able to explain 63.1% of the variance in GSCP. The findings of this study serve as a pivotal yardstick for guiding corporate policy formulation, offering valuable insights to drive continuous improvements in supply chain management and performance. Furthermore, the research holds substantial implications for managerial strategies by shedding light on the potential of GIC and EP to elevate GSCP. Positioned as one of the initial studies to delve into the moderating role of EP in the relationship between GIC and GSCP, this research offers insights within an emerging market context.
Keywords: 650; Green intellectual capital; green supply chain; supply chain performance; external pressures; emerging economy; egypt